Perfusion process with tangential flow filtration for oncolytic VSV-GP production - Hamusics, Orsolya; Wittmann, Anja; Hasler, Katrin; Müller, Sabrina; Birk, Daniel; Gorr, Ingo H.; Brix, Alexander; Soza-Ried, Jorge (Frontiers in Bioengineering and Biotechnology, 2025)
The oncolytic vesicular stomatitis (VSV)-GP virus is a promising therapeutic against cancer. To ensure clinical efficacy, doses with high titers are required, which poses a challenge for the manufacturing process. Perfusion cultivation processes with high cell densities have attracted great interest to improve the production titer. This work aimed to enhance the titer of the VSV-GP production process with suspension human embryonic kidney 293 (HEK293) cells by using perfusion with tangential flow filtration (TFF) and virus retention. For this purpose, six potential critical process parameters were evaluated using I-optimal design of experiments (DoE). The study showed that several input parameters and their interactions have significant impact on the infectious titer. Increasing the seeding cell density significantly improved the infectious titer, allowing infection at up to 46.6 × 106 cells mL-1 without decrease in the cell-specific virus yield. Keeping the perfusion pause after infection at minimum (1.1–1.3 h) and subsequently start the perfusion with a higher exchange rate (0.045–0.051 nL cell-1 d-1) was shown to be beneficial. The process was sensitive to shear stress and thus, the optimal crossflow rate was between 44 and 55 mL min-1, which corresponds to 950–1150 s-1 shear rate. By optimizing the perfusion process, the titer reached up to 5.1 × 1010 TCID50 mL-1, which is 17-fold higher than in batch cultivation. Overall, this work presents perfusion cultivation as an efficient technology to improve the VSV-GP titer with virus retention.